Thermal Properties of Woven Kenaf/Carbon Fibre-Reinforced Epoxy Hybrid Composite Panels. (11th December 2019) - Aisyah, H. A.; Paridah, M. T.; Sapuan, S. M.; Khalina, A.; Berkalp, O. B.; Lee, S. H.; Lee, C. H.; Nurazzi, N. M.; Ramli, N.; Wahab, M. S.; Ilyas, R. A.
Abstract : The effects of carbon fibre hybridisation on the thermal properties of woven kenaf-reinforced epoxy composites were studied. Woven kenaf hybrid composites of different weave designs of plain and satin and fabric counts of 5 × 5 and 6 × 6 were manually prepared by a vacuum infusion technique. A composite made from 100% carbon fibre was served for a comparison purpose. Thermal properties of pure carbon fibre and hybrid composites were determined by using a thermogravimetric analyser (TGA) and differential scanning calorimeter (DSC). It was found that a hybrid composite with higher kenaf fibre content (fabric count 6 × 6 ) showed better thermal stability while the highest thermal stability was found in the pure carbon fibre composite. The TG and DTG results showed that the amount of residue decreased in the plain-designed hybrid composite compared to the satin-designed hybrid composite. The DSC data revealed that the presence of woven kenaf increased the decomposition temperature.